Exploitation, Altruism, and Social Welfare: An Economic Exploration - Matthias Doepke (Institute for the Study of Labor (IZA), 2013)
Child labor is often condemned as a form of exploitation. I explore how the notion of exploitation, as used in everyday language, can be made precise in economic models of child labor. Exploitation is defined relative to a specific social welfare function. I first show that under the standard dynastic social welfare function, which is commonly applied to intergenerational models, child labor is never exploitative. In contrast, under an inclusive welfare function, which places additional weight on the welfare of children, child labor is always exploitative. Neither welfare function captures the more gradual distinctions that common usage of the term exploitation allows. I resolve this conflict by introducing a welfare function with minimum altruism, in which child labor in a given family is judged relative to a specific social standard. Under this criterion, child labor is exploitative only in families where the parent (or guardian) displays insufficient altruism towards the child. I argue that this welfare function best captures the conventional concept of exploitation and has useful properties for informing political choices regarding child labor.
Keywords: D63; D64; J10; J47; J80; 330; child labor; exploitation; social welfare function; altruism; Kinderarbeit; Marxistische Arbeitstheorie; Soziale Wohlfahrtsfunktion; Eltern; Altruismus; Theorie